The social function of the press about awareness of peaceful coexistence - Rashed Abed, Shaima (Opción, 2019)
The world is undergoing many political, social, economic, technological and other changes in terms of violence or terrorism. The world has also witnessed many in- cidents of violence, conflict, war, disasters and crises of all kinds. These conditions have led to intolerance, increased violence and hatred among individuals and peo- ples alike, as well as sectarian, ethnic and religious distinction among the people of one nation. In general, the media have the ability to reach a wide audience and thus have a social responsibility to promote the idea of peaceful coexistence, to foster a culture of dialogue, to promote tolerance among its members and to renounce the phenomenon of intolerance, violence and atonement. The printed press is one of the means of mass communication that has an effective role in spreading this cul- ture, as it has characteristics and characteristics that distinguish it from other mod- ern means of communication. It allows readers to control the time of their reading and re-read their contents, and they contain intricate topics with precise details that play a role in building intellectual, behavioral, cultural, political and social patterns. The methodological framework of the study included an introduction to the importance of the media and print media, research problem, the importance of research and its objectives, type and methodology of research, as well as the socie- ty and sample of research. As for the theoretical framework of the study, it focused on three axes: the dimensions of the social function of print journalism, what are the most common issues of peaceful coexistence in society, and the role of newspa- pers in educating the public about peaceful coexistence. The practical framework focused on clarifying the procedures of the study in terms of the methodology used in the study and the study society and its limits and tools and the statistical methods used, as well as the procedures of honesty and consistency of study and finally the results of the analytical study.At the end of the research, the researcher concluded that the Iraqi newspa- pers play a large role in raising awareness about the concepts and issues of peaceful coexistence. The most prominent issues focused on the awareness campaigns carried out by Iraqi newspapers are the issue of renunciation of violence and hatred. The researcher recommended dealing with issues that create dialogue and involve Iraqi citizens in addressing some societal issues, especially those related to peaceful coexistence, as well as the need for Iraqi newspapers to rely on reliable sources, in-depth coverage and an- alytical vision when presenting a community issue and offering solutions.